Sex education, awareness and perception among adolescents: a cross sectional study from Central Kerala - Anilkumar, Angitha; Varghese, Ann Mary; Mathews, Chris Joseph; Paul, Sandra; Sajan, Manasa Maria; Joseph, Sruthi Ann; Jose, Betsy A. (International Journal Of Community Medicine And Public Health, 2022)
Background: Teenagers exhibit little awareness of, or interest in, the normal processes of puberty, sexual health, pregnancy, or reproduction. They also have limited knowledge of sexual and reproductive fitness. Because sexual education is a lifelong process, it should be a fundamental component of development and understanding beginning in adolescence and continuing into adulthood. Methods: A cross-sectional study was undertaken among Central Kerala school students in the adolescent age group (13-18 years) with both genders. The students were provided with a pre-tested questionnaire on their knowledge, attitudes, and perceptions of sex education as well as a proforma on the socio demographic details. Results: The majority of research participants 30.1% were 17 years old, although the average age was 16 (±1.43 years). 67.9% of the participants were girls, and 32.1% were boys. Sex of the participant has association with knowledge, attitude and perception on sex education. Socio demographic factors tend to affect the knowledge. In the present study, attitude towards sex education has association with the sex of the participant and the syllabus they are studying. Conclusions: Just over half of the pupils have adequate understanding about sexual education. This demonstrates the importance of delivering sex education classes for adolescent kids on a regular basis. School based educational classes can be promoted wherein, a more familiar and comfortable person like the teachers, who are trained by medical professionals, can impart the adequate knowledge to the students.